Determinants of Fertility among Women of Childbearing Age in North Sulawesi Province, Indonesia - Solang, Sesca D.; Maitimo, Brigitte Inez; Winokan, Jeanny J.; Pratiwi, Dian; Bohari, Bohari (Open Access Macedonian Journal of Medical Sciences, 2021)
AIM: This study aims to determine the determinants associated with the productivity of women of childbearing age in North Sulawesi Province. METHODS: The research design used is an analytic study with a cross-sectional approach. This research uses the raw data of the North Sulawesi Province Program Performance and Accountability Survey (SKAP) of 2019. The sample of this study was all women of childbearing age (15–49 years), married and unmarried in North Sulawesi Province based on the SKAP raw data of 2019, totaling 1454 women of childbearing age. The variables in this study consisted of independent and dependent variables. The independent variables in this study were age, education, marital status, the ideal number of children, decision using contraception, age at first sexual intercourse, and contraceptive use in women of childbearing age. RESULTS: Fertility with >2 children is 349 people (24.01%). There is a significant relationship between age, education, marital status, ideal number of children, the decision to use contraception, age at first sexual intercourse, and use of contraception on fertility with p < 0.05. The multivariate test showed that ideal children (odds ratio [OR] 5.555), age (OR 5.619), age at first sexual intercourse (OR 9,486), and use of contraception (OR 0.450). CONCLUSION: The age of sexual intercourse had the most significant influence on the fertility of women of childbearing age with an OR of 9.486. This indicates that the age at sexual intercourse in women of childbearing age will affect fertility 10 times compared to other variables, namely, the ideal number of children, age, and use of family planning.